Phosphorylation and Dephosphorylation of the Presequence of Precursor MULTIPLE ORGANELLAR RNA EDITING FACTOR3 during Import into Mitochondria from Arabidopsis . Issue 2 (24th August 2015) - Law, Yee-Song; Zhang, Renshan; Guan, Xiaoqian; Cheng, Shifeng; Sun, Feng; Duncan, Owen; Murcha, Monika W.; Whelan, James; Lim, Boon Leong
Abstract : Phosphorylation of the presequence of an RNA editing factor by cytosolic kinases and its dephosphorylation by an outer mitochondrial membrane phosphatase contribute to mitochondrial import of the factor protein. Abstract: The nucleus-encoded mitochondria-targeted proteins, multiple organellar RNA editing factors (MORF3, MORF5, and MORF6), interact with Arabidopsis ( Arabidopsis thaliana ) PURPLE ACID PHOSPHATASE2 (AtPAP2) located on the chloroplast and mitochondrial outer membranes in a presequence-dependent manner. Phosphorylation of the presequence of the precursor MORF3 (pMORF3) by endogenous kinases in wheat germ translation lysate, leaf extracts, or STY kinases, but not in rabbit reticulocyte translation lysate, resulted in the inhibition of protein import into mitochondria. This inhibition of import could be overcome by altering threonine/serine residues to alanine on the presequence, thus preventing phosphorylation. Phosphorylated pMORF3, but not the phosphorylation-deficient pMORF3, can form a complex with 14-3-3 proteins and HEAT SHOCK PROTEIN70. The phosphorylation-deficient mutant of pMORF3 also displayed faster rates of import when translated in wheat germ lysates. Mitochondria isolated from plants with altered amounts of AtPAP2 displayed altered protein import kinetics. The import rate of pMORF3 synthesized in wheat germ translation lysate into pap2 mitochondria was slower than that into wild-type mitochondria, and this rate disparity was not seen for pMORF3 synthesized in rabbit reticulocyte translation lysate, the latter translation lysate largely deficient in kinase activity. Taken together, these results support a role for the phosphorylation and dephosphorylation of pMORF3 during the import into plant mitochondria. These results suggest that kinases, possibly STY kinases, and AtPAP2 are involved in the import of protein into both mitochondria and chloroplasts and provide a mechanism by which the import of proteins into both organelles may be coordinated.